Micropropagação e desenvolvimento vegetativo de mirtilo - Ferri, Juçara (2008)
Blueberry cultivation is recent in Brazil, and the area expansion of this production is limited by the lack of quality seedlings. The in vitro propagation make possible, in little time, to produce of mass form, high quality plants. In this work, the first objective was to study some involved factors in the establishment, multiplication and rooting of blueberry rabbiteye group, seeking yield increase of the seedlings production through micropropagation. The second objective was to study some involved factors seedlings development of the Aliceblue, Climax, O Neal and Georgiagem cultivars, seeking make available to producers seedlings sufficiently developed and adapted to orchard implantation. The work was developed in 2 stages. The first stage was constituted for 4 trials micropropagation related, and consisted respectively in the in vitro establishment, multiplication of the material previously in vitro established and rooting sprout obtained in the multiplication stage. Was verified that zeatin is necessary for in vitro establishment Powderblue and Florida cultivars, be able to utilize the smaller concentration (9 μM). Cultivars Woodard, Bluebelle and Bluegem explants presented the most bud number. The most rooting percentage was obtained with 6 µM of IBA added in culture media. The basal stakes presented the most root quantity. The 6 µM concentration of growth regulator ANA provide the most root length. The second stage of this work was constituted for 2 trials vegetative establishment related. In the first trial were utilized 2 blueberry cultivars of rabbiteye group and 4 substrates tips. In the second trial were utilized 2 cultivars blueberry group and 4 substrates tips. It recommended 70% sawdust + 20% coconut fiber + 10% bovine manure mixture to the most growth aerial part, the most mass of dry matter aerial and root, and the most sprout number. For the rabbiteye group, Climax cultivar presented the most vegetative development, parallel O´Neal cultivar highbush group.